State Composite Innovation Indicator (SCII): a methodology for evaluating regional innovation systems - Beneli, Daniela Scarpa; Carvalho, Silvia Angélica Domingues de [UNESP]; Furtado, André Tosi (FapUNIFESP (SciELO), 2022)
The methodological systematization of data collection, compilation and aggregation of Science, Technology and Innovation Indicators has proved to be an important component in the formulation and evaluation of public policies. Thus, the aim of this article is to present a methodology for the construction of the State Composite Innovation Indicator that allows evaluating the innovative performance of regional innovation systems. The procedures used were: research by bibliographic materials, adaptation of the methodology proposed by the European Innovation Scoreboard and calculation of the databases available in the Brazilian statistical system. The methodology of the State Composite Innovation Indicator revealed strengths and weaknesses in the different dimensions of Brazilian regional innovation systems. Among them, in São Paulo, Rio Grande do Sul, Paraná and Rio de Janeiro, there were strength in human resources and research system, in the Amazon, on the other hand, there are weaknesses in these same dimensions and highlighting innovators and occupations.
Indicador composto estadual de inovação (ICEI): uma metodologia para avaliação de sistemas regionais de inovação
Keywords: expenditure on Science; impact; innovative activity; technology and innovation